EVALUASI KESTABILAN LUBANG BUKAAN DAN SISTEM PENYANGGAAN BERDASARKAN KLASIFIKASI GEOMEKANIKA PADA TAMBANG BATUBARA BAWAH TANAH SD-C2 LORI 1 DI PT. NUSA ALAM LESTARI, KOTA SAWAHLUNTO. - Yudi Andrian; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2021)
Underground mining is a mining system in which all activities take place below the earth's surface. In practice in the field, mining is carried out by making tunnels as access for lorries and opening paths and then opening branches using the Room and Pillar method. This research was conducted to determine rock strength, rock mass class, potential for wedge failure, stability of the hole opening, and recommendations for the appropriate support system based on rock mass rating and distance of the support. Based on the results of the analysis at a RMR value of 61,63 and 66 the FK value <1.5 using an average buffer distance of 2.01 m, it is necessary to change the distance between the supports to get a stable FK value (≥1.5). From the calculation results to achieve a stable FK value, at a RMR 61,63,and 66 the exact buffer distance ranges from 1.8 m - 2.1 m.